Series Resonant LED Driver with Current Equalization Based on the Differential-Mode Transformer - Kuo-Ing Hwu; Jun-Yi Lee (Energies)
In this research, a series resonant LED driver circuit based on the differential-mode transformer for current equalization is proposed. In this circuit, the series resonant converter adopts controlled frequency modulation to change the energy transferred to the output while realizing zero voltage switching (ZVS) turn-on of the half-bridge switch. To deal with the problem of unequal LED currents caused by two different forward conduction voltages of the output LED strings, a differential-mode transformer is employed to balance the currents between the two LED strings, and the relationship between the magnetizing inductance and the percentage of current sharing error are derived to facilitate the design. Furthermore, only the current of one LED string needs to be sensed to achieve current equalization, while the current of the other LED string is automatically determined by the differential-mode transformer.